The Future of Ageing in Europe Making an Asset of Longevity - Walker, Alan.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book provides the most comprehensive analysis available of the challenges created by Europe's ageing population. Grounded in state-of-the-art scientific assessments by leading European researchers, the book is strongly policy focused. Indeed this book contains a detailed account of the policies required across a broad field, from economic sustainability and extending working lives, to healthy ageing, technological innovation, long term care and political citizenship, for the successful adaptation to the challenges of ageing in Europe and globally. It is a policy manifesto to ensure that the future of ageing in Europe is transformed into a highly beneficial one for both citizens and societies.
1. Introduction -- 2. Strategies of Active Ageing in Europe -- 3. Achieving Economic Sustainability in Ageing Societies -- 4. Effective and Sustainable Private Pensions -- 5. Extending Working Lives -- 6. Healthy Life Years and Social Engagement -- 7. Improving Health in Later Life: How a Life Course Approach Could Improve Health and Well-Being in Old Age -- 8. Technology for All -- 9. Social Support and Long Term Care for Older People - The Potential for Social Innovation and Active Ageing -- 10. Promoting the Political Inclusion and Participation of Older People: Social, Psychological and Institutional Perspectives -- 11. Conclusion: Realising Active Ageing.
Keywords: Aging; Social policy; Ageing; Social Policy